Enhancing Students’ Listening Comprehension with English Songs - Supriyani, Supriyani; Fatin, Rhaudya Maghfira (STIBA IEC JAKARTA, 2025)
The focus of this study is to figure out whether implementing English songs as learning resources and media in educational activities may enhance students' listening skills. The researchers used a quantitative approach and pre-experimental study on 39 pupils in class VIII-B at MTs Darul Falah Bongas to gather this data. The researchers employed a single group pre-test and post-test design, which is a form of pre-experimental study. Ten multiple-choice questions based on song lyrics with a gap-filling task design were employed. The findings demonstrated that using English songs as media significantly improved students' listening skills. By comparing the pre-test and post-test results, this conclusion was reached. The mean score before the test was 41.38, and the mean score after the test was 65.69. Additionally, the hypothesis result displays a value of 5.81, which is bigger than the t-table (i.e., 2.03<5.81>2.72). The authors draw the conclusion that, in addition to being interested and motivated in the learning process, their listening abilities increased after being taught using English songs as medium. Their listening skills can then be greatly enhanced by selecting the appropriate English music.